Determinant factors of family welfare among Bogor online riders on pandemic COVID-19 - Nikmatul Khoiriyah; Euis Sunarti; Melly Latifah (HUMANITAS published by Universitas Ahmad Dahlan., 2022)
COVID-19 pandemic impacted economic activity, including a decrease in the number of online motorcycle taxi passengers due to large-scale social restrictions. This study aimed to analyze the effect of determinant factors: work source of stress, self-efficacy, coping strategies, and symptoms of stress on the family welfare among online motorcycle taxi drivers. This study also analyzed the differences of all research variables according to years of service (less or more than two years). A cross-sectional design involving 120 online drivers in Bogor who were selected by convenience sampling was applied in this study. All research instruments used in data collection have good reliability. Data was collected by filling out a structured questionnaire shared with a google form, considering the pandemic conditions. Data was analyzed inferentially using SPSS and Smart PLS. Different test results showed that drivers who worked less than two years had lower earnings before and during the pandemic but performed higher coping strategies than those who worked more than two years. Self-efficacy positively affects online motorcycle taxi drivers' family welfare during the pandemic, objectively and subjectively. While work source of stress negatively affects subjective family welfare only.